Kristus (dan) Debata Mulajadi na Bolon: Perjumpaan yang “serupa tapi ‘tak sama” atau “adalah?” - Carel Hot Asi Siburian (Jurnal Teologi Kontekstual Indonesia, 2023)
Christ and Debata Mulajadi na Bolon are two distinct entities, understood respectively by Christianity and by Batak-Toba culture. Christ is known as the incarnate logos (John 1:1-5) and the firstborn and invisible image of God (Colossians 1:15), while Debata Mulajadi na Bolon is only approached as “the supreme god of Batak-Toba”; although the titles ascribed to him are similar to those ascribed to God. This article will build on the idea that Christ is Debata Mulajadi na Bolon himself, although it must be acknowledged that there are differences, especially in their Trinity theology. Debata Mulajadi na Bolon is not a pagan figure but God who presents Himself as Debata Mulajadi na Bolon. The three biblical texts that will be discussed in this article are the bridge of this transformation effort, also using two approaches namely Niebuhr’s typology, Christ the Transformer of Culture and Bevans’ synthesized contextual theology model.